Toward the theory of the Sobolev classes with critical exponent - O.S. Afanas’eva; V.I. Ryazanov; R.R. Salimov (Доповiдi Нацiональної академiї наук України, 2019)
It is established that an arbitrary homeomorphism f in the Sobolev class W1,n−1loc with the outer dilatation K0(x,f)∈Ln−1loc is the socalled lower Q - homeomorphism with Q=K0(x,f) and the ring Q* homeomorphism with Q∗=Kn−10(x,f). These results make it possible to research the local and boundary behaviors of the mappings W1,n−1loc